Investigating Attitudes towards Financial Literacy in Schools: An Impact Study - KOH, Noi Keng (Journal of Education and Vocational Research, 2012)
The global economic downturn has highlighted the damaging impact of financial illiteracy on individuals, families, communities and entire nations. The need to teach people how to spend, save, invest, borrow and manage money wisely has become more important than ever. It has also raised questions about what it takes to effectively engage people and change their financial behavior. This study is part of a larger study in Singapore schools to study the impact of an initiative to equip teacher’s with pedagogical skills and knowledge to integrate financial literacy messages in day-to-day lessons and foster a socially responsible attitude towards managing money to create a financially sustainable society. This study provides insights into how financial education can be integrated into classroom lessons in schools to deal with challenges that living in modern society presents.